Turkish Banking Sector’s Profitability Factors - ACARAVCI, Songül Kakilli; ÇALIM, Ahmet Ertuğrul (International Journal of Economics and Financial Issues, 2012)
profitability of banking sector is the most important instrument of financial system for the future of the economy. The objective of this study is to determine by using Johansen and Juselius cointegration test approach of the bank specific and macroeconomic factors that affect the profitability of commercial banks in Turkish banking sector. In study, the data are collected from the three biggest state-owned, privately-owned and foreign banks. The sample period spans from 1998 to 2011. In the study, return of asset, return of equity and net interest margin were used as proxy for profitability of banks. The bank specific determinants, which were thought to have effects on profitability are total credits/total assets, total deposits/total assets, total liquid assets/total assets, total wage and commission incomes/ total assets, total wage and commission expenses/total assets, the logarithm of total assets and total equity/total assets. The macroeconomic determinants of study are real gross domestic product, inflation rate, real exchange rate and real interest rate. Empirical findings suggest that the bank specific determinants have been more effect than macroeconomic factors on profitability of the banks. The reel gross domestic product and real exchange rate have been effective on the profitability. In addition, the 2001 economic crisis has a negative effect on all Turkish Banking sector. Keywords: Profitability of banking; banking performance; deposit banks; the net interest margin; time series analysis. JEL Classifications: G21; M20